The lower stratum families in the Neo-Assyrian period - Galil, Gershon. (Culture and history of the ancient Near East,, 2007)
This pioneering study wrestles with the perpetual problem of the structure of the Neo-Asssyrian society. Part I of this volume surveys all 446 Lower Stratum families in the period under review (800-600 B.C.), mentioned in 177 texts, mainly legal transactions, administrative records, court decisions, and letters. It also examines the terminology, the formulation of the texts, and the status of these families. Part II of this volume considers socio-economic and demographic issues, including family types, family size, marriage patterns, childless families, single-parent families, and more. It is the most important and the most responsible study of the lower stratum of Neo-Assyrian society proposed to date, and it will be the point of departure of every study of this field in the future.